Association of human cytomegalovirus DNAaemia and specific granzyme B responses in lung transplant recipients. (6th August 2013) - Weseslindtner, L.; Kerschner, H.; Steinacher, D.; Kundi, M.; Jaksch, P.; Simon, B.; Hatos‐Agyi, L.; Scheed, A.; Klepetko, W.; Puchhammer‐Stöckl, E.
Summary In lung transplant recipients (LTRs), human cytomegalovirus (HCMV) DNAaemia could be associated with HCMV disease and reduced allograft survival. In the present study we analysed whether or not HCMV‐specific granzyme B (Grz‐B) responses indicating CD8+ T cell cytotoxicity exert an impact on HCMV DNAaemia and relate to specific interferon (IFN)‐γ secretion. HCMV‐specific Grz‐B responses were quantitated by enzyme‐linked immunosorbent assay (ELISA) in 70 samples from 39 HCMV seropositive LTRs who were prospectively investigated for HCMV DNA plasma levels and IFN‐γ kinetics using a standardized CD8+ T cell assay (QuantiFERON®‐CMV assay). In all LTRs who were protected from HCMV DNAaemia by early and persistent IFN‐γ responses, Grz‐B responses were also detected. In LTRs who developed episodes of HCMV DNAaemia, the Grz‐B responses which were detected prior to viral DNA detection differed significantly in patients who experienced episodes with high (exceeding 1000 copies/ml) and low plasma DNA levels (P = 0·0290, Fisher's exact test). Furthermore, the extent of Grz‐B release prior to viral DNAaemia correlated statistically with the detected levels of IFN‐γ (P < 0·0001, Spearman's rank test). Of note, simultaneous detection of Grz‐B and IFN‐γ secretion was associated significantly with protection from high HCMV DNA plasma levels during the subsequent follow‐up (P = 0·0057, Fisher's exact test), and this association was stronger than for IFN‐γ detection alone. We conclude that, in addition to IFN‐γ responses, Grz‐B secretion by CD8+ T cells is essential to control HCMV replication and a simultaneous measurement of IFN‐γ and Grz‐B could contribute to the immune monitoring of LTRs.